Toussaintâ??s Clause : The Founding Fathers and the Haitian Revolution - Brown, Gordon S., 1936- (Book collections on Project MUSE., 2005)
In its formative years, America, birthplace of a revolution, wrestled with a volatile dilemma. John Adams, Thomas Jefferson, Alexander Hamilton, and many other founding fathers clashed. What was to be the new republic's strategy toward a revolution roiling just off its shores? From 1790 to 1810, the disagreement reverberated far beyond Caribbean waters and American coastal ports. War between France and Britain, the great powers of the time, raged on the seas and in Europe. America watched aghast as its trading partner Haiti, a rich hothouse of sugar plantations and French colonial profit, expl.